The quest for The wicker man history, folklore and pagan perspectives - Franks, Benjamin; Harper, Stephen 1971-; Murray, Jonathan 1973-; Stevenson, Lesley; Carpenter, Gary 1951- (Luath Press Limited, 2006)
Front Cover -- Half-Title Page -- Title Page -- Copyright Page -- Contents -- Introduction: The search for The Wicker Man -- The Genesis of The Wicker Man -- The Wicker Man, May Day and the Reinvention of Beltane -- Ritualistic Behaviour in The Wicker Man: A classical and carnivalesque perspective on 'the true nature of sacrifice' -- Sacrifice, Society and Religion in The Wicker Man -- Anthropological Investigations: An innocent exploration of The Wicker Man culture -- The Folklore Fallacy: A folkloristic/filmic perspective on The Wicker Man -- The Wicker Man - Cult Film or Anti-Cult Film? Parallels and paradoxes in the representation of Paganism, Christianity and the law -- The Wicca Woman: Gender, sexuality and religion in The Wicker Man -- 'Do As Thou Wilt': Contemporary Paganism and The Wicker Man -- Music and Paganism with Special Reference to The Wicker Man -- Wicker Man, Wicker Music -- Interview with Robin Hardy -- Notes on Contributors
Keywords: Electronic books; Wicker man (Motion picture); Aufsatzsammlung